Calidad del servicio y satisfacción del cliente externo de las oficinas especiales 2 del Banco de la Nación en la ciudad de Iquitos mayo 2020 - Vargas La Torre, Linda Iveth (2021)
The research work Quality of Service and External Customer Satisfaction of the Special Offices 2 Bank of the Iquitos Nation, May 2020, had as its main objective to determine the relationship between the quality of the service and the level of customer satisfaction external offices of the Special Offices 2 Bank of the Iquitos Nation, May 2020; It is correlational level with a quantitative approach of non-experimental and cross-sectional design, the sample consisted of 425 external clients. The results showed that in the special offices 2 Bank of the Iquitos Nation Iquitos, RENIEC and the Superior Court of Justice of Loreto have a low positive relationship but it is not significant and the offices of El Dorado and the National University of the Peruvian Amazon have a relationship positive low and is significant. The research concludes stating that the relationship between the quality of the service and the level of satisfaction of the external clients of the Special Offices 2 Bank of the Iquitos Nation, is positive low with a Spearman Rho Correlation Coefficient, 0.188 * * and significant at the 0.01 level, with p = 0.000.